The practice of Usrah in teaching and learning: case study at the International Islamic University Malaysia - Awang Abdul Muizz Awang Marusin; Suraya Sintang; Mohd. Azri Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2018)
The purpose of this study is to analyse Usrah Mahallah in the International Islamic University Malaysia (IIUM), application of usrah therein and its contributions in improving teaching and learning approaches. As the focus of this study is much qualitative, a case study was conducted and so become the only method that can realise the purpose of this study. Findings shown that Usrah Mahallah is widely accepted by IIUM resident students participated in usrah. Small ratio of usrah leader to usrah participants, contemporary and friendly approaches applied by usrah leaders, organisation of attractive Usrah activities at both residential college and IIUM levels and flexibility and conduciveness of usrah settings established and maintained jointly by Usrah leaders and participants are among key factors that contributed to such acceptance. Those findings lead to the fact that Usrah Mahallah is not only a progressive product of Islamisation in IIUM and a tool to develop students’ social, spiritual and intellectual values and skills, but also an effective approach to teaching and learning, especially in Islamic education.